Sustainability in mining, minerals and energy: New processes, pathways and human interactions for a cautiously optimistic future - Moran, Chris; Lodhia, S.; Kunz, N.; Huisingh, D. (Elsevier, 2014)
© 2014 Published by Elsevier Ltd. All rights reserved.The supply of minerals and energy is critical to global society. However, this supply is associated with social and environmental impacts, leading to concerns of generational and intergenerational equity. In light of these concerns, a call for papers for a special volume on the mining industry was issued with the view that such academic work could assist in reducing the negative impacts associated with this industry. This paper introduces the Special Volume "The sustainability agenda of the minerals and energy supply and demand network: An integrative analysis of ecological, ethical, economic, and technological dimensions". The Special Volume contains 84 articles, divided into several themes; sustainability accounting and reporting, corporate social responsibility, future mining challenges, integrative frameworks for sustainability, management aspects, mining in a developing context and new frontiers in the oil andgas industry. The Special Volume also includes two letters on contemporary issues with commentaries on these from experts in the fields, viz., community conflict and land rehabilitation. Insights obtained across these themes are summarized and recommendations are made of what is needed to build upon the findings of this Special volume. A research agenda is proposed for the future from the gaps and synergies identified. The overall contribution of this Special Volume is that it renews the debate on the sustainability challenges for the mining industry and provides transdisciplinary insights into resolving some of these challenges.